2017
DOI: 10.1089/acm.2016.0391
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cardiac Autonomic Tone Following Long Sudarshan Kriya Yoga in Art of Living Practitioners

Abstract: The results suggest that long SKY induces significant oscillations in cardiac autonomic tone. Parasympathetic activity increases and sympathetic activity decreases and sympathovagal balance improves following long SKY. Decrease in sympathetic activity is also demonstrated by decrease in conductance although it did not reach statistical significance. From this study it can be concluded that long SKY has a beneficial effect on cardiac autonomic tone, and psychophysiological relaxation. It may serve as a tool to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
0
28
0
1
Order By: Relevance
“…Following long Sudarshan Kriya Yoga, Bhaskar et al . [ 23 ] reported that LF decreased and HF increased. On the other hand, Telles et al .…”
Section: Introductionmentioning
confidence: 99%
“…Following long Sudarshan Kriya Yoga, Bhaskar et al . [ 23 ] reported that LF decreased and HF increased. On the other hand, Telles et al .…”
Section: Introductionmentioning
confidence: 99%
“…Such autonomic benefits were seen for all subjects, independent of age [32,33], even though the magnitude of such effects appeared to be higher for older than for younger adults, according to Pal and colleagues [34].…”
Section: Discussionmentioning
confidence: 86%
“…A SKY program involves slow Ujjayi breathing (diaphragmatic breathing) with inhalatory and exhalatory pauses, followed by fast-paced Bhastrika pranayama (rapid breathing) and cyclic rhythmic breathings. The breathings in a SKY program occur in slow, medium, and fast frequencies (Bhaskar, Kharya, Deepak, & Kochupillai, 2017).…”
Section: Discussionmentioning
confidence: 99%